2004
DOI: 10.1016/j.molcel.2004.09.032
|View full text |Cite
|
Sign up to set email alerts
|

p53 Linear Diffusion along DNA Requires Its C Terminus

Abstract: In cells, sequence-specific transcription factors must search through an entire genome to find their target sites in promoters. Such sites may be identified by using one-dimensional (linear diffusion) and/or three-dimensional (association/dissociation) mechanisms. We show here that wild-type p53 possesses the ability to linearly diffuse on DNA. p53 lacking its C terminus is incapable of such sliding along DNA, while the isolated C terminus of p53 is even more effective than the full-length protein at one-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
198
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(217 citation statements)
references
References 49 publications
16
198
1
2
Order By: Relevance
“…This was confirmed by a study showing that p53 transcriptional activity is activated by PAb421 in cells (Lu and Lane, 1993). Recent studies have demonstrated that within the context of chromatin or supercoiled DNA, the C-terminal domain may actually facilitate binding of the core to its target DNA sequence by providing an additional anchorage to specific DNA sites via nonspecific DNA binding (Espinosa and Emerson, 2001;McKinney and Prives, 2002;McKinney et al, 2004).…”
Section: Structural Basis For Mutant P53 Reactivationmentioning
confidence: 68%
“…This was confirmed by a study showing that p53 transcriptional activity is activated by PAb421 in cells (Lu and Lane, 1993). Recent studies have demonstrated that within the context of chromatin or supercoiled DNA, the C-terminal domain may actually facilitate binding of the core to its target DNA sequence by providing an additional anchorage to specific DNA sites via nonspecific DNA binding (Espinosa and Emerson, 2001;McKinney and Prives, 2002;McKinney et al, 2004).…”
Section: Structural Basis For Mutant P53 Reactivationmentioning
confidence: 68%
“…Many factors may contribute to the DNA bending; other parts of the protein or base pairs flanking the p53-response elements may also be involved in triggering additional conformational change and in stabilizing the bent DNA conformation. There is evidence indicating that efficient p53 binding requires both the core domain and the C-terminal domain of the p53 protein 46,47 . In addition, base pairs other than the central 4 could also contribute to different extents.…”
Section: Discussionmentioning
confidence: 99%
“…McKinney and Prives, 59 Fojta et al, 60 and Palecek et al 61 have shown that the CTD is important for binding to various non-linear DNAs. In another study, McKinney et al 62 have demonstrated the involvement of CTD in the ability of p53 to diffuse linearly on DNA. Both, McKinney et al 62 and Liu et al 63 showed as well that the CTD is required for efficient promoter activation in vivo by p53.…”
Section: The P53 C-terminal Dna-binding Domainmentioning
confidence: 95%
“…In another study, McKinney et al 62 have demonstrated the involvement of CTD in the ability of p53 to diffuse linearly on DNA. Both, McKinney et al 62 and Liu et al 63 showed as well that the CTD is required for efficient promoter activation in vivo by p53. Moreover, Harms and Chen 64 have recently reported that the CTD inhibits p53-dependent induction of IGFBP3 gene.…”
Section: The P53 C-terminal Dna-binding Domainmentioning
confidence: 95%